Fission‐Fusion Group Dynamics and Cooperative Hunting Stabilise Social Carnivore Populations - J. M. Fryxell; S. Mduma; J. Masoy; J. Grant C. Hopcraft; A. R. E. Sinclair; R. Dejeante; C. Packer (Ecology Letters, 2025)
Theory suggests that large social groups of carnivores should be unsustainable, due to reduced foraging efficiency because of overlapping perception radii. Using Serengeti lions as a case study, we apply behaviourally based foraging models to show that fragmentation of social groups into smaller subgroups or mutual cooperation during hunting are both plausible hypothetical mechanisms capable of sustaining larger lion prides. Data from the Serengeti ecosystem demonstrate that lion prides typically fragment into small hunting groups that are well approximated by an exponential distribution of group sizes typical of fission‐fusion social systems. A model linking fission‐fusion group dynamics with predator–prey interaction predicts both the surprising degree of population stability of the Serengeti lions as well as the long‐term persistence of large prides. There is little evidence, however, that Serengeti lions cooperate during hunting except when they hunt Cape buffalo, so fission‐fusion is apparently the dominant stabilising process in Serengeti.

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Evolving Perspectives of Stewardship in the Seafood Industry - Robert Blasiak; Alice Dauriach; Jean-Baptiste Jouffray; Carl Folke; Henrik Österblom; Jan Bebbington; Frida Bengtsson; Amar Causevic; Bas Geerts; Wenche Grønbrekk; Patrik J. G. Henriksson; Sofia Käll; et al. (Frontiers in Marine Science, 2021)
Humanity has never benefited more from the ocean as a source of food, livelihoods, and well-being, yet on a global scale this has been accompanied by trajectories of degradation and persistent inequity. Awareness of this has spurred policymakers to develop an expanding network of ocean governance instruments, catalyzed civil society pressure on the public and private sector, and motivated engagement by the general public as consumers and constituents. Among local communities, diverse examples of stewardship have rested on the foundation of care, knowledge and agency. But does an analog for stewardship exist in the context of globally active multinational corporations? Here, we consider the seafood industry and its efforts to navigate this new reality through private governance. We examine paradigmatic events in the history of the sustainable seafood movement, from seafood boycotts in the 1970s through to the emergence of certification measures, benchmarks, and diverse voluntary environmental programs. We note four dimensions of stewardship in which efforts by actors within the seafood industry have aligned with theoretical concepts of stewardship, which we describe as (1) moving beyond compliance, (2) taking a systems perspective, (3) living with uncertainty, and (4) understanding humans as embedded elements of the biosphere. In conclusion, we identify emerging stewardship challenges for the seafood industry and suggest the urgent need to embrace a broader notion of ocean stewardship that extends beyond seafood.

Biology and biotechnological applications of microalgae and photosynthetic prokaryotes: part 2 - Julian J. Eaton-Rye; Benoit Guieysse; Michael A. Packer; Tina C. Summerfield; Susanna A. Wood (New Zealand Journal of Botany, 2020)

Invasion syndromes: a systematic approach for predicting biological invasions and facilitating effective management - Ana Novoa; David M. Richardson; Petr Pyšek; Laura A. Meyerson; Sven Bacher; Susan Canavan; Jane A. Catford; Jan Čuda; Franz Essl; Llewellyn C. Foxcroft; Piero Genovesi; Heidi Hirsch; et al. (Biological Invasions, 2020)
Our ability to predict invasions has been hindered by the seemingly idiosyncratic context-dependency of individual invasions. However, we argue that robust and useful generalisations in invasion science can be made by considering “invasion syndromes” which we define as “a combination of pathways, alien species traits, and characteristics of the recipient ecosystem which collectively result in predictable dynamics and impacts, and that can be managed effectively using specific policy and management actions”. We describe this approach and outline examples that highlight its utility, including: cacti with clonal fragmentation in arid ecosystems; small aquatic organisms introduced through ballast water in harbours; large ranid frogs with frequent secondary transfers; piscivorous freshwater fishes in connected aquatic ecosystems; plant invasions in high-elevation areas; tall-statured grasses; and tree-feeding insects in forests with suitable hosts. We propose a systematic method for identifying and delimiting invasion syndromes. We argue that invasion syndromes can account for the context-dependency of biological invasions while incorporating insights from comparative studies. Adopting this approach will help to structure thinking, identify transferrable risk assessment and management lessons, and highlight similarities among events that were previously considered disparate invasion phenomena.

Biology and biotechnological applications of microalgae and photosynthetic prokaryotes: Part 1 - Julian J. Eaton‐Rye; Benoit Guieysse; Michael A. Packer; Tina C. Summerfield; Susanna A. Wood (New Zealand Journal of Botany, 2019)

The diversification of neopasiphaeine bees during the Cenozoic (Hymenoptera: Colletidae) - Eduardo A. B. Almeida; Laurence Packer; Gabriel A. R. Melo; Bryan N. Danforth; Sophie C. Cardinal; Fábio B. Quinteiro; Marcio R. Pie (Zoologica Scripta, 2019)
The biogeography of colletid bees as a whole can be explained by several South American‐Australian trans‐Antarctic interchanges. Within Colletidae, neopasiphaeine bees form a large group that has not been adequately studied, even though they are interesting both from the biogeographical viewpoint for fitting well the austral Gondwanan track and for their associations to host plants. The present paper integrates phylogenetic, biogeographic and paleontological data to reconstruct the evolutionary history of Neopasiphaeinae, with special emphasis on the New World taxa, relating the evolution of these bees to changes, such as the Andes uplift and expansion of open vegetation biomes. First, we propose a phylogenetic hypothesis for the Neopasiphaeinae using one mitochondrial and five nuclear loci. Phylogenetic relationships and divergence time estimation were simultaneously inferred in a Bayesian framework, and the tempo of neopasiphaeine diversification was investigated using lineage‐through‐time plots. The historical biogeography of neopasiphaeine bees was investigated in a likelihood framework. The clade represented by Neopasiphaeinae is strongly supported within Colletidae, and the bulk of their genera can be divided into two major sister‐clades that diverged during the Eocene: one endemic to the Australian region and the other to the Neotropical region. Divergence times among most neotropical genera of Neopasiphaeinae indicate that they differentiated and started their diversification during the Miocene. Our results depict a complex process of geographic evolution in the Neotropical clade, which probably relates to important changes in the neotropical climates and biota beginning at the Oligocene and became more marked in the Miocene. We present a scenario of the neotropical Neopasiphaeinae initially associated with areas of open vegetation in subtropical and temperate portions of South America, followed by multiple separations of lineages east and west of the Andes, and more recent occupations of habitats in tropical portions of the continent.

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

Impact of intensive fish farming on methane emission in a tropical hydropower reservoir - Marcelo Gomes da Silva; Ana Paula Packer; Fernanda G. Sampaio; Luciano Marani; Ericka V. C. Mariano; Ricardo A. A. Pazianotto; Willian J. Ferreira; Plínio C. Alvalá (Climatic Change, 2018)

A ‘dynamic’ landscape of fear: prey responses to spatiotemporal variations in predation risk across the lunar cycle - M. S. Palmer; J. Fieberg; A. Swanson; M. Kosmala; C. Packer (Ecology Letters, 2017)
Ambiguous empirical support for ‘landscapes of fear’ in natural systems may stem from failure to consider dynamic temporal changes in predation risk. The lunar cycle dramatically alters night‐time visibility, with low luminosity increasing hunting success of African lions. We used camera‐trap data from Serengeti National Park to examine nocturnal anti‐predator behaviours of four herbivore species. Interactions between predictable fluctuations in night‐time luminosity and the underlying risk‐resource landscape shaped herbivore distribution, herding propensity and the incidence of ‘relaxed’ behaviours. Buffalo responded least to temporal risk cues and minimised risk primarily through spatial redistribution. Gazelle and zebra made decisions based on current light levels and lunar phase, and wildebeest responded to lunar phase alone. These three species avoided areas where likelihood of encountering lions was high and changed their behaviours in risky areas to minimise predation threat. These patterns support the hypothesis that fear landscapes vary heterogeneously in both space and time.

Introduction: proceedings of the 2015 New Zealand symposium on algae and photosynthetic prokaryotes - Michael A. Packer; Julian J. Eaton‐Rye; Tina C. Summerfield; Benoit Guieysse; Susanna A. Wood (New Zealand Journal of Botany, 2017)

Recombinant human heterodimeric IL-15 complex displays extensive and reproducible N- and O-linked glycosylation - M. Thaysen-Andersen; E. Chertova; C. Bergamaschi; E. S. X. Moh; O. Chertov; J. Roser; R. Sowder; J. Bear; J. Lifson; N. H. Packer; B. K. Felber; G. N. Pavlakis (Glycoconjugate Journal, 2016)

Algal and cyanobacterial bioenergy and diversity - Julian J. Eaton‐Rye; Michael A. Packer; Tina C. Summerfield; Susanna A. Wood (New Zealand Journal of Botany, 2014)

The case for fencing remains intact - C. Packer; A. Swanson; S. Canney; A. Loveridge; S. Garnett; M. Pfeifer; A. C. Burton; H. Bauer; D. MacNulty (Ecology Letters, 2013)
Creel et al . argue against the conservation effectiveness of fencing based on a population measure that ignores the importance of top predators to ecosystem processes. Their statistical analyses consider, first, only a subset of fenced reserves and, second, an incomplete examination of ‘costs per lion.’ Our original conclusions remain unaltered.

Conserving large carnivores: dollars and fence - C. Packer; A. Loveridge; S. Canney; T. Caro; S.T. Garnett; M. Pfeifer; K.K. Zander; A. Swanson; D. MacNulty; G. Balme; H. Bauer; C.M. Begg; et al. (Ecology Letters, 2013)
Conservationists often advocate for landscape approaches to wildlife management while others argue for physical separation between protected species and human communities, but direct empirical comparisons of these alternatives are scarce. We relate African lion population densities and population trends to contrasting management practices across 42 sites in 11 countries. Lion populations in fenced reserves are significantly closer to their estimated carrying capacities than unfenced populations. Whereas fenced reserves can maintain lions at 80% of their potential densities on annual management budgets of $500 km −2 , unfenced populations require budgets in excess of $2000 km −2 to attain half their potential densities. Lions in fenced reserves are primarily limited by density dependence, but lions in unfenced reserves are highly sensitive to human population densities in surrounding communities, and unfenced populations are frequently subjected to density‐independent factors. Nearly half the unfenced lion populations may decline to near extinction over the next 20–40 years.

Effects of Trophy Hunting on Lion and Leopard Populations in Tanzania - C. PACKER; H. BRINK; B. M. KISSUI; H. MALITI; H. KUSHNIR; T. CARO (Conservation Biology, 2011)
Tanzania holds most of the remaining large populations of African lions ( Panthera leo ) and has extensive areas of leopard habitat ( Panthera pardus ), and both species are subjected to sizable harvests by sport hunters. As a first step toward establishing sustainable management strategies, we analyzed harvest trends for lions and leopards across Tanzania's 300,000 km 2 of hunting blocks. We summarize lion population trends in protected areas where lion abundance has been directly measured and data on the frequency of lion attacks on humans in high‐conflict agricultural areas. We place these findings in context of the rapidly growing human population in rural Tanzania and the concomitant effects of habitat loss, human‐wildlife conflict, and cultural practices. Lion harvests declined by 50% across Tanzania between 1996 and 2008, and hunting areas with the highest initial harvests suffered the steepest declines. Although each part of the country is subject to some form of anthropogenic impact from local people, the intensity of trophy hunting was the only significant factor in a statistical analysis of lion harvest trends. Although leopard harvests were more stable, regions outside the Selous Game Reserve with the highest initial leopard harvests again showed the steepest declines. Our quantitative analyses suggest that annual hunting quotas be limited to 0.5 lions and 1.0 leopard/1000 km 2 of hunting area, except hunting blocks in the Selous Game Reserve, where harvests should be limited to 1.0 lion and 3.0 leopards/1000 km 2 .

Increased genetic differentiation in a specialist versus a generalist bee: implications for conservation - Amro Zayed; Laurence Packer; Jennifer C. Grixti; Luisa Ruz; Robin E. Owen; Haroldo Toro (Conservation Genetics, 2006)

Conservation Genetics of Potentially Endangered Mutualisms: Reduced Levels of Genetic Variation in Specialist versus Generalist Bees - LAURENCE PACKER; AMRO ZAYED; JENNIFER C. GRIXTI; LUISA RUZ; ROBIN E. OWEN; FELIPE VIVALLO; HAROLDO TORO (Conservation Biology, 2005)
Oligolectic bees collect pollen from one or a few closely related species of plants, whereas polylectic bees visit a variety of flowers for pollen. Because of their more restricted range of host plants, it maybe expected that specialists exist in smaller, more isolated populations, with lower effective population sizes than generalists. Consequently, we hypothesized that oligolectic bees have reduced levels of genetic variation relative to related polylectic species. To test this hypothesis, we used five phylogenetically independent pairs of species in which one member was oligolectic and the other was polylectic. We assayed genetic variation in our species pairs at an average of 32 allozyme loci. Within each species pair, the oligolectic member had fewer polymorphic loci, lower average allelic richness, and lower average expected heterozygosity than its polylectic relative. Averaged over all species pairs, this corresponds to a 21% reduction in allelic richness, a 72% reduction in the proportion of polymorphic loci, and an 83% reduction in expected heterozygosity in specialists compared with generalists. Our data support the hypothesis of reduced effective population size in oligolectic bees and suggest that they may be more prone to extinction as a result. We suggest that in instances in which bee specialists are involved in mutually codependent relationships with their floral hosts, these mutualisms may be endangered for genetic and ecological reasons.